Mutualistic presence of normal Flora in Human Intestine: A review (Journal of Bio-Science, 2015)
Human body contains a huge number of micro-organisms in its intestine. It is ten times more in number compared to the number of human body cells. These micro-organisms are mainly anaerobic bacteria and perform useful functions in relation to development of gut, and production of vitamins and hormones. These bacteria also perform a wide range of metabolic functions. The present article reviews briefly the mutualistic relationship of intestinal flora with human intestine along with their pathogenic behaviour to some extent. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22515 J. bio-sci. 21: 21-25, 2013